ANTIPHOSPHOLIPID-LIKE SYNDROME INDUCED BY COVID19: A CASE REPORT STUDY - Petrusevska Marinkovic, Sanja; Anastasovski, Ankcia; Todorovska, Lidija (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Many patients with severe COVID-19 present with coagulation abnormalities associated with severe infections, such as disseminated intravascular coagulation or trombotic mycroangiopathy.  Thatâ€™s why is important to pay attention to the differential diagnoses of COVID-19 and other diseases following thrombotic events. Antiphospholipid syndrome is an autoimmune disorder characterized by thrombosis. The diagnosis criteria for antiphospholipid syndrome are based on the detection of abnormal levels of at least one of the most common antiphospholipid antibodies . In this study, we discuss the relationship between COVID-19, antiphospholipid syndrome and antiphospholipid syndrome -like phenomenon, and thrombosis that may occur. We present  a 60-year-old woman hospitalized for COVID-19 and pneumonia with a moderately severe clinical picture. During the hospitalization under anticoagulant therapy, she developed coagulation disorders with prolonged active partial thromboplastin time, positive lupus anticoagulant and positive beta-2glycoprotein. The coagulation disorder is in addition to antiphospholipid syndrome, which is associated with the possibility of bleeding in the patient. Elevated levels of the isotypes of antiphospholipid antibodies in COVId-19 patients create antiphospholipid syndrome-like condition. Considering the high rate of mortality due to coagulation abnormalities and thrombosis among COVID-19 patients, it is important to pay attention to the differential diagnoses of COVID-19 and other diseases following thrombotic events, as well as their implication on the therapeutic approach to patients. Current data recommend the use of prophylactic anticoagulation with low molecular weight heparin in hospitalized patients with COVID-19 regardless of the severity of the clinical picture.    Key words: COVID-19, antiphospholipid syndrome, antiphospholipid antibodies, coagulation  disorders, thrombosis, lupus anticoagulant, anti-beta 2 glycoprotein I (anti-b2GPI), immune disorders, antimalarials, anticoagulant therapy, plateled agonists